Gold Nanoparticles: Multifunctional Properties, Synthesis, and Future Prospects - Hatice Duman; Emir Akdaşçi; Furkan Eker; Mikhael Bechelany; Sercan Karav (Nanomaterials)
Gold nanoparticles (NPs) are among the most commonly employed metal NPs in biological applications, with distinctive physicochemical features. Their extraordinary optical properties, stemming from strong localized surface plasmon resonance (LSPR), contribute to the development of novel approaches in the areas of bioimaging, biosensing, and cancer research, especially for photothermal and photodynamic therapy. The ease of functionalization with various ligands provides a novel approach to the precise delivery of these molecules to targeted areas. Gold NPs’ ability to transfer heat and electricity positions them as valuable materials for advancing thermal management and electronic systems. Moreover, their inherent characteristics, such as inertness, give rise to the synthesis of novel antibacterial and antioxidant agents as they provide a biocompatible and low-toxicity approach. Chemical and physical synthesis methods are utilized to produce gold NPs. The pursuit of more ecologically sustainable and economically viable large-scale technologies, such as environmentally benign biological processes referred to as green/biological synthesis, has garnered increasing interest among global researchers. Green synthesis methods are more favorable than other synthesis techniques as they minimize the necessity for hazardous chemicals in the reduction process due to their simplicity, cost-effectiveness, energy efficiency, and biocompatibility. This article discusses the importance of gold NPs, their optical, conductivity, antibacterial, antioxidant, and anticancer properties, synthesis methods, contemporary uses, and biosafety, emphasizing the need to understand toxicology principles and green commercialization strategies.